2023
DOI: 10.1002/anie.202300538
|View full text |Cite
|
Sign up to set email alerts
|

Fucose Migration Pathways Identified Using Infrared Spectroscopy**

Abstract: Fucose is a ubiquitous monosaccharide associated to major classes of glycans. A main obstacle to the sequencing of fucosylated glycans is the migration of fucose, which leads to misinterpretations in mass spectrometry analysis. Here, using ion vibrational spectroscopy, we resolve the structure of fucosylated fragments of Lewis and blood group H antigen trisaccharides and we unveil the position and linkage of the fucose after migration. Our findings demonstrate that the structure of fragment ions resulting from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…In recent work, Moge et al reported 33 the rearrangement product of fucose-containing disaccharides that carried a fucose attached by an α(1 → 6) bond to GlcNAc. The rearrangement product that features a similar glycosidic linkage, [an16 + H] + , is among the most stable isomers and is more stable by 2.0 and 3.9 kcal mol −1 than, respectively, the α and β-anomers of Le a .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In recent work, Moge et al reported 33 the rearrangement product of fucose-containing disaccharides that carried a fucose attached by an α(1 → 6) bond to GlcNAc. The rearrangement product that features a similar glycosidic linkage, [an16 + H] + , is among the most stable isomers and is more stable by 2.0 and 3.9 kcal mol −1 than, respectively, the α and β-anomers of Le a .…”
Section: Resultsmentioning
confidence: 99%
“…Products of fucose migration in (B) T2-derived antigens 32 and in (C) a series of Fuc -GlcNAc disaccharides. 33 the theoretical calculations, inconclusive. In the study of Mucha et al, the IR spectra of the two ions showed enough difference to conclude that the fucose rearrangement is rather unlikely.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether the organic compounds are natural products or synthesized by chemists, it is extremely important to determine their structures and absolute conformations at the atomic level. Over the past few decades, numerous researchers have developed and refined many methods for the structural identification of organic molecules, such as nuclear magnetic resonance ( NMR ), infrared spectroscopy ( IR ), mass spectrometry ( MS ), single crystal X-ray diffraction ( X-ray SCD ), etc. Among them, X-ray SCD can provide direct and accurate structural information and is globally recognized as a fairly reliable method for the structural identification of organic compounds, including their stereochemical conformation.…”
mentioning
confidence: 99%